When using the substitution method, the easiest way to start off is to make sure you have one equation set to equal either y or x. That would give you:
y=-x+1
-4x+4y=12
Then, you put the equation set to y inside the other equation to get:
-4x+4(-x+1)=12
You would the solve the equation to get:
-4x-4x+4=12
-8x+4=12
-8x=8
x=-1
Now you still have to find the y value. You would now put the x value inside either of the equations and solve it. I chose the first one and got:
2(-1)+2y=2
-2+2y=2
2y=4
y=2
Your answer is (-1,2).